UJI AKTIVITAS ANTIBAKTERI EKSTRAK KASAR BIJI BUAH LANGSAT (Lansium domesticum Corr.) terhadap Bakteri Staphylococcus aureus - ., Wastri Gusniyani Manik (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: increasing number of Staphylococcus aureus resistant toantimicrobial medicine makes traditional medicine commonly used. Previousresearch which investigate langsat seed infuse effect to Salmonella typhishows negative result, so that research is continued by replacing the langsatseed infuse to crude extract. Objective: The aim of this study was toinvestigate secondary metabolite and antibacterial activity of ethanol 96%extract and n-Hexane extract of Lansium domesticum Corr. seed throughMinimum Inhibitory Concentration (MIC) and Minimum BactericidalConcentration (MBC) measurement. Method: this research was anexperimental study with complete randomized design and posttest onlycontrol group design. Phytochemical screening performed by test tubemethod. Antibacterial activity test determined by tube dilution method in100%; 50%; 25%; 12,5%; 6,25%; 3,125%; 1,56%; 0,78%; 0,39%; and 0,19%concentrations. Positive control contained bacterial suspension and agarmedium, negative control contained extract dilution and agar medium, andsolvent control contained tween 20 solution, bacterial suspension and agarmedium. Results: Secondary metabolite content of ethanol 96% extract ofLansium domesticum Corr. were alkaloids, flavonoids, saponins, tannins,phenols, and terpenoids. Secondary metabolite content of n-hexane extract ofLansium domesticum Corr. were saponins, and terpenoids. MIC of ethanol96% extract and n-hexane extract could not be measured because of turbiditywhich caused by tween 20 solution. MBC of ethanol 96% extract obtained in100% concentration, while MBC of n-hexane extract in 100% and 50%concentration. Conclusion: Crude extracts of Lansium domesticum Corr.seed has antibacterial activity against staphylococcus aureus.Keywords: Antibacterial, Crude extracts of Lansium domesticum Corr.,Staphylococcus aureus, 1) Medical School, Faculty of Medicine, University of Tanjungpura Pontianak,West Kalimantan. 2) Biology Departement, Mathematic and Science Faculty, University ofTanjungpura Pontianak, West Kalimantan. 3) Pharmacology Departement, Medical School, Faculty of Medicine,University of Tanjungpura Pontianak, West Kalimantan.